Ideias de alunos sobre o "seu" passado doloroso a Guerra Colonial Portuguesa - Alves, Luís Alberto Marques (2012)
When one mentions identity, European conscientiousness, tolerance, civic intervention, soli-darity... History is requested to perform a predominantly social role and function. On the oth-er hand, when one asks to the European youth about the significance of History, we can see in their responses the "valorisation of History as a source of learning" and the respect for the monumentality of the past. The project that we are presenting, "Enseigner les passés doulou-reux en Europe", has the clear purpose of avoiding forgetfulness, bring historic density that guarantees the correct knowledge of the past, provide the students with critical competences to assume the responsibilities of the "memory duties". The focus of this research is to try to understand how young people think about the question of the historic reparation as, for in-stance, ponder about the justification, viability, motives and effects of the reparation of historic injustice. These reflections are an important window to the historic conscientiousness of young people: by observing how they think about the matter of historic reparation, we can see how they conceive the limits of individual and collective responsibility and also the moral responsibility of the State and its citizens.